GABAB Agonists for the Treatment of Alcohol Use Disorder - Mirijello, Antonio; Caputo, Fabio; Vassallo, Gabriele; Rolland, Benjamin; Tarli, Claudia; Gasbarrini, Antonio; Addolorato, Giovanni (Current Pharmaceutical Design, 2015)
Almost 10% of the world’s population is affected by alcohol use disorder (AUD). The combination between psychosocial intervention and pharmacological treatment seems to be the most effective approach for patients affected by AUD. Among effective drugs useful in the treatment of AUD, GABAB-ergic medications have been tested with encouraging results (i.e. sodium oxybate, baclofen, gabapentin, pregabalin and tiagabine). The present review will summarize available data on these medications.
Keywords: pharmacological treatment